Desenvolvimento de ferramenta para mapeamento diagnóstico de riscos: estudo do caso da Biblioteca Central da UFMG - Rafael Vilela Silveira (2020)
This research sees the conservation of collections as the present institutional function of the Library's physical space. For this reason, it aims to investigate the role of these buildings as envelopes to protect their collections. It is a complex construction typology, often characterized as territories with multiple roles, conflicts, crossing institutional dynamics, and diversity of uses and occupations, as in the Central Library of the Federal University of Minas Gerais (BC-UFMG). Such complexity implies challenges for managing and maintaining its infrastructure and preserving the collection, achieved only through disciplinary connections from different areas. The case study involves assessing conditions for conservation of the Special Collections Division of the University Library, located at the building. Aspects related to the building's infrastructure and its interrelationships with the materiality of the collection, institutional policies, and security issues are highlighted, all of which are relevant for establishing the context in managing Cultural Heritage risks. The procedure starts from analyzing the risks incurred on the collection; and culminates in its systematization through exploration of assessment presentation instruments developed by the field of Post-Occupancy Assessment: the discovery maps. Adaptations made on them allows create a preventive tool named collections potential risks proximity map, derived from infrastructure physical elements. This tool is applicable in research case study, being able to assist its collection storage rooms design and administrative actions. It is a way to enhance the dialogue between Architecture and Conservation, allowing the continuous establishment of conjugated parameters to help decision making in libraries. The results suggest the building's constructive elements – its architectural conception and its conservation status – as conditioning factors for preserving the collections in the case study.